2010
DOI: 10.3746/jkfn.2010.39.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Property and Antioxidative Activity of Hot-Water Extracts from Enzyme Hydrolysate of Astragalus membranaceus

Abstract: To enhance the yield and bioactivity of hot-water extract from herbal medicine, Astragalus membranaceus was hydrolyzed with carbohydrases, such as ClariSEB and Fungamyl. After hot-water extracts were prepared from each hydrolysate (HW-C/F), physicochemical property, antioxidant activity and sensory property were evaluated. The solid content ( o Brix) of HW-C/F was higher than hot-water extract from A. membranaceus no treated enzyme (control). Although pH of HW-C/F was lower than that of the control, the acidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recently, there has been an increasing preference for foods that gratify palatability, nutrition, and physiologic functions to prevent aging and chronic diseases. Various studies are being made of functional foods and ingredients in academic and industrial circles ( Kwon et al, 2010 ). As the frequency of dine-out has increased all over the world, the consumption of fast foods and convenient meat products has increased rapidly, which implies a need for the production of functional fresh meat ( Zhang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increasing preference for foods that gratify palatability, nutrition, and physiologic functions to prevent aging and chronic diseases. Various studies are being made of functional foods and ingredients in academic and industrial circles ( Kwon et al, 2010 ). As the frequency of dine-out has increased all over the world, the consumption of fast foods and convenient meat products has increased rapidly, which implies a need for the production of functional fresh meat ( Zhang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analisis penghambatan α-amilase dilakukan dengan menggunakan metode modifikasi dari Penelitian Kwon (Kwon et al, 2007). Sebanyak 50 µl sampel dicampur dengan 250 µl α-amilase dari babi pankreas kemudian ditambahkan 250 µl buffer sodium fosfat 0,02 M (pH 6,9).…”
Section: Metodeunclassified
“…For centuries, some Asian countries have used Euonymus alatus (EA), an edible plant, for medicinal purposes in the treatment of several conditions, including cancer, hyperglycemia, menstrual discomfort, diabetic complications, and detoxification [ 1 , 2 ]. The Korean Food Code recognizes the young leaves of EA as registered food material.…”
Section: Introductionmentioning
confidence: 99%
“…Some components such as rutin, quercetin (QCT), and kaempferol extracted from Euonymus spp. have been reported to exhibit antioxidant activity [ 1 , 2 , 3 , 4 ]. Moreover, our previous studies demonstrated that the ethanolic extract of EA leaves can improve learning and memory impairment in scopolamine-treated mice and further promote Nrf2-mediated antioxidative activity in the hippocampal region [ 5 ].…”
Section: Introductionmentioning
confidence: 99%